Implementation of a laboratory for the outdoor characterization of photovoltaic technologies under the climatic conditions of Lima: Collaboration with the XXIII Peruvian Symposium on Solar Energy - Conde Mendoza, Luis Angel (2020)
This paper presents the design, implementation and first results of a Photovoltaic Research Laboratory developed at the facilities of the Materials Science and Renewable Energy Group (MatER-PUCP) of the Pontifical Catholic University of Peru in collaboration with the IDEA Research Group (Research and Development in Solar Energy) of the University of Jaen (UJA), Spain. This laboratory is one of the first in the country with the appropriate equipment for calibration and certification of different commercial and emerging technologies of photovoltaic modules in the Peruvian market. The results that are expected to be obtained through an extensive experimental campaign, which began in May 2019, may be offered to companies or other public institutions, such as detailed studies of the behavior and degradation of the different technologies of photovoltaic modules depending on the particular climatic conditions from the city of Lima (irradiance levels and diffuse component, operating temperature, humidity, spectral distribution, and dust).